Late Breaking Abstract - A phase I feasibility study in establishing the role of ultrasound-guided pleural biopsies in pleural infection (The AUDIO study) - Psallidas, I; Kanellakis, N; Bhatnagar, R; Ravindran, R; Yousuf, A; Edey, A; Mercer, R; Corcoran, J; Hallifax, R; Shetty, P; Dong, T; Piotrowska, H; et al. (European Respiratory Society, 2017)
Pleural infection is a common complication of pneumonia associated with high mortality and poor clinical outcome. We performed a feasibility interventional clinical trial assessing the safety and significance of ultrasound (US)-guided pleural biopsy culture to increase the microbiological yield.